Serum lipidomic analysis from mixed neutron/X-ray radiation fields reveals a hyperlipidemic and pro-inflammatory phenotype - Laiakis, Evagelia C. (Sci Rep, 2019)
Heightened threats for nuclear terrorism using improvised nuclear devices (IND) necessitate the development of biodosimetry assays that could rapidly assess thousands of individuals. However, the radiation exposures from an IND may be complex due to mixed fields of neutrons and photons (γ-rays), shielding from buildings, and proximity to the epicenter among others. In this study we utilized lipidomics to analyze serum samples from mice exposed to various percentages of neutrons and X-rays to a total dose of 3 Gy. Triacylglycerides, phosphatidylserines, lysophosphatidylethanolamines, lysophosphatidylcholines (LPCs), sphingolipids, and cholesteryl esters all showed delayed increases at day 7 compared to day 1 after irradiation, while diacylglycerides decreased in mixed field exposures and phosphatidylcholines (PCs) remained largely unchanged. Individual lipid molecules with a high degree of unsaturation exhibited the highest fold changes in mixed fields compared to photons alone. More importantly, the increased ratio of LPCs to PCs of each irradiation group compared to control could be used as a radiation biomarker and highlights the existence of a pro-inflammatory phenotype. The results showed that even a small percentage of neutrons in a mixed field can lead to high biological responses with implications for accurate biodosimetry, triage and medical managements of exposed populations.